The application of gene transfer technology in articular cartilage tissue engineering: An insight - Ahmad Radzi, Muhammad Aa'zamuddin; Abdulahi Hashi, Abdurezak; Azhim, Azran; Sha'ban, Munirah (Persatuan Genetik Malaysia (Genetics Society of Malaysia), 2017)
Degenerative disease of osteoarthritis (OA) may be caused by untreated injury or trauma to articular cartilage. The use of gene transfer technology in conjunction with tissue engineering has been suggested as having the potential to treat cartilage injuries. The combination may even reverse the degenerative changes that lead to OA. Various genes that are responsible for specific protein production that stimulate the regeneration and restoration of cartilage have been identified. This paper serves to fill the dearth of literature that examine the use of the combination of gene transfer technology and tissue engineering to address OA. This study explores the patterns and trends of publications that describe the application of gene transfer technology in articular cartilage tissue engineering (ACTE). Using selected terms, a search was conducted on the published articles indexed in Elsevier’s SCOPUS and Thomson Reuter’s Web of Science™ Core Collection related to gene transfer technology in ACTE. It can be appreciated that the number of publications related to the association of gene transfer technology and ACTE is low. The present findings suggest that ACTE has yet to fully utilize the gene transfer technology that introduces functional genes into the targeted cells. Among the most commonly used genes reported in the publications are Transforming Growth Factor-Beta 1 (TGF-β1), TGF-β3, Bone Morphogenetic Protein 2 (BMP-2), Interleukin-1 Receptor Antagonist (IL-1Ra), Sex Determining Region Y-box9 (SOX9), and Insulin-like Growth Factor I (IGF-I). The introduction of these functional genes was achieved by using either viral or non-viral gene delivery systems. It is hoped that further studies will be done to examine the potential application of gene transfer technology in ACTE. Their combination can be used for cartilage regeneration to treat osteoarthritic condition.